THE ROLE OF INVERTASES IN ANTHER DEHISCENCE - Komrsova, Marie (2023)
The opening of anthers to release pollen (anther dehiscence) is a complex, regulated process. One of the mechanisms contributing to anther dehiscence is the active removal of water from anthers. Invertases are plant enzymes which cleave sucrose into glucose and fructose, changing the osmotic potential, suggesting they may have a role in water movement in the anthers. Invertase expression has been investigated by qRT-PCR in A. thaliana buds of different developmental stages to determine which genes are upregulated as dehiscence happens. As jasmonic acid has been shown to regulate water movement in anther dehiscence, the expression of invertases in a dad1, the A. thaliana mutant which does not produce jasmonic acid, and the phenotypes of A. thaliana invertase KO mutants have also been investigated. Invertase isoforms INVH, INVD, CWINV2, and CWINV4 are upregulated in A. thaliana buds during late stages but downregulated in the absence of JA, while CINV2 and VACINV are upregulated in absence of JA. Single knockout mutants in these genes however did not show a striking phenotype, but the expression patterns of closely related genes indicate they may be acting redundantly. Double mutant cwinv2cwinv4 did not have an impaired phenotype, so CRISPR/Cas9 gene targets were instead explored as an option to produce quadruple mutant cwinv1cwinv2cwinv4cwinv5. β-glucuronidase reporter constructs have been prepared to investigate the localization of INVH, INVD, CWINV2, CWINV4, CINV2 and VACINV throught flower development in WT and in dad1.